Renewable Energy accelerating the energy transition - Goyal, Rahul (Springer, 2024)
This book reveals key challenges to ensuring the secure and sustainable production and use of energy resources and provides corresponding solutions. This book covers the advanced technologies applied in renewable energy generation, energy storage, an alternative to petroleum fuels, waste to energy, solar energy, the impact of fossil fuel combustion on the environment, green buildings, social sustainability, etc. It goes beyond theory and describes practical challenges and solutions associated with energy and sustainability. This book is of particular interest to graduate students and academic or industrial researchers/professionals working in renewable energy, sustainability, bioenergy, and mechanical and automobile engineering. This book makes a forceful foundation for the establishment of the role of renewable energy in energy transition for a sustainable, cleaner, and greener future. This book is unique compared to other available books because it covers a wide variety of topics on a single platform.
Keywords: bicssc; bisacsh; Energy policy; Energy and state; Renewable energy sources; Hardcover, Softcover / Technik/Wärmetechnik, Energietechnik, Kraftwerktechnik